Climbing the ladder of health technology utilization: facilitators and dynamic mechanism of clinicians’ contrast-enhanced ultrasound utilization in China - Yuhang Zheng; Yuehua Chen; Shiyin Wu; Qingwen Deng; Wenbin Liu (BMC Cancer)
Abstract Background Promoting health technology utilization is essential for improving the capability of disease diagnosis and treatment. Nevertheless, the knowledge-product nature of health technology seems to be ignored, and different levels of technology utilization have seldom been investigated. This study took Contrast-enhanced ultrasound (CEUS) as an example to identify different levels of technology utilization and investigate the facilitators of clinicians’ CEUS use in China and the dynamic mechanism for upgrading technology utilization, which would benefit from studying the general pattern of health technology dissemination and utilization. Methods A structured questionnaire survey with multi-stage random sampling was conducted between February and August 2019. Clinicians who were aware of CEUS and worked at the liver disease-related departments of sampled health institutions in Jiangxi and Fujian provinces were invited to participate in the survey. Multilevel regression analysis was conducted to determine factors influencing different levels of health technology utilization, and structural equation modeling was applied to validate theoretical hypotheses for developing the dynamic mechanism model. Results A total of 289 clinicians were included. The average scores for symbolic, conceptual, and instrumental utilization were 2.497 ± 1.190, 1.719 ± 1.536, and 1.668 ± 1.452, respectively. It indicated that clinicians’ CEUS utilization was clustered in the same hospital. Market pressure (β = 0.221, P < 0.01) and organizational support (β = 0.278, P < 0.001) were significantly associated with symbolic utilization; subjective norms(β = 0.154, P < 0.01), organizational support (β = 0.228, P < 0.001), and organizational culture (β=-0.155, P < 0.01) were significantly linked to conceptual utilization; and perceived ease of use (β = 0.085, P < 0.05) was positively relevant to instrumental utilization. Additionally, there was a significant impact of symbolic utilization on conceptual utilization (β = 0.668, P < 0.001), as well as conceptual utilization on instrumental utilization (β = 0.843, P < 0.001). Conclusions This study evaluated the key influences on CEUS utilization at three levels, and then constructed a theoretical model of the dynamic mechanisms that drive technology utilization to a higher level. It will fill gaps in knowledge about the dynamics mechanisms of climbing the ladder of technology utilization, and provide practical guidance for promoting the wider utilization of CEUS and other health technologies. Some recommendations for clinicians and managers were also proposed from individual and organizational perspectives.